Dampak Perubahan Kebijakan Moneter Terhadap Stabilitas Mata Uang di Negara Berkembang - Khaerudin Sidik Patoni; Andi Thamrin; Amir Buhang; Nurjanna Ladjin; Yofandi Djibran Himran (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the impact of monetary policy changes on currency stability in developing countries. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are In implementing monetary policy, the central bank has a crucial role in achieving economic stability in a developing country, some of these roles include controlling inflation, maintaining currency stability, regulating interest rates, maintaining balanced economic growth, providing certainty and guidance going forward, conducting open market operations, and stabilizing the financial system. Changes in monetary policy in a developing country will have an impact on currency stability in that country. Therefore, appropriate and effective monetary policy can help maintain currency stability, and can help control inflation, encourage economic growth, and increase export competitiveness.